Critical evaluation of magnetic resonance imaging targeted, transrectal ultrasound guided transperineal fusion biopsy for detection of prostate cancer - Kuru, Timur Hasan; Röthke, Matthias C.; Seidenader, Jonas Nikolaus; Simpfendörfer, Tobias; Boxler, Silvan; Alammar, Khalid; Rieker, Philip; Popeneciu, Valentin; Roth, Wilfried; Pahernik, Sascha; Schlemmer, Heinz-Peter; Hohenfellner, Markus; et al. (The journal of urology, 2013)
Purpose: Diagnosis and precise risk stratification of prostate cancer is essential for individualized treatment decisions. Magnetic resonance imaging/transrectal ultrasound fusion has shown encouraging results for detecting clinically significant prostate cancer. We critically evaluated magnetic resonance imaging targeted, transrectal ultrasound guided transperineal fusion biopsy in routine clinical practice. Materials and Methods: Included in this prospective study were 347 consecutive patients with findings suspicious for prostate cancer. Median age was 65 years (range 42 to 84) and mean prostate specific antigen was 9.85 ng/ml (range 0.5 to 104). Of the men 49% previously underwent transrectal ultrasound guided biopsies, which were negative, and 51% underwent primary biopsy. In all patients 3 Tesla multiparametric magnetic resonance imaging was done. Systematic stereotactic prostate biopsies plus magnetic resonance imaging targeted, transrectal ultrasound guided biopsies were performed in those with abnormalities on magnetic resonance imaging. Imaging data and biopsy results were analyzed. A self-designed questionnaire was sent to all men on further clinical history and biopsy adverse effects. Results: Of 347 patients biopsy samples of 200 (58%) showed prostate cancer and 73.5% of biopsy proven prostate cancer were clinically relevant according to National Comprehensive Cancer Network (NCCN) criteria. On multiparametric magnetic resonance imaging 104 men had findings highly suspicious for prostate cancer. The tumor detection rate was 82.6% (86 of 104 men) with a Gleason score of 7 or greater in 72%. Overall targeted cores detected significantly more cancer than systematic biopsies (30% vs 8.2%). Of 94 patients without cancer suspicious lesions on magnetic resonance imaging 11 (11.7%) were diagnosed with intermediate risk disease. Regarding adverse effects, 152 of 300 patients (50.6%) reported mild hematuria, 26% had temporary erectile dysfunction and 2.6% needed short-term catheterization after biopsy. Nonseptic febrile urinary tract infections developed in 3 patients (1%). Conclusions: Magnetic resonance imaging targeted, transrectal ultrasound guided transperineal fusion biopsy provides high detection of clinically significant tumors. Since multiparametric magnetic resonance imaging still has some limitations, systematic biopsies should currently not be omitted. The morbidity of the transperineal saturation approach is reasonable and mainly self-limiting.
Gesehen am 21.07.2021